THE RELATIONSHIP BETWEEN FAMILY FUNCTIONING WITH SELF-INJURY BEHAVIOR TOWARDS YOUNG ADULTS - M. Rafly Adam; Nastiti, Dwi (Journal of Social Science, 2025)
Objective: The purpose of this study is to investigate the relationship between the functioning of the family and the self-injury among a Young adult in Candi Sayang, Sidoarjo. Method: Using a correlational quantitative approach. The participants are teenagers aged 17 to 25, totaling 47 individuals. Data was obtained using measurement tools in the form of a family functioning scale and a self-injury scale, then analyzed using the Product Moment correlation statistical method. Results: The results of the data analysis showed a correlation coefficient of r = -0.96 with a p value of 0.000 (Sig. < 0.05), indicating a significant negative relationship between family functioning and self-injury in Young adult. It can be concluded that the higher the family functioning, the lower the self-injury among young adult. Conversely, if family functioning is low, self-injury tends to be higher. Novelty: This study highlights the strong inverse correlation between family functioning and self-injury among young adults in a specific regional context (Candi Sayang, Sidoarjo), which has not been widely explored in prior research. The use of a high correlation value (r = -0.96) suggests a particularly strong association that adds depth to the understanding of family dynamics in mental health outcomes during young adulthood.